2017
DOI: 10.21613/gorm.2016.676
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Does not Have Any Impact on Ovarian Reserve Markers in Infertile Women

Abstract: OBJECTIVE:To evaluate the potential role of vitamin D on ovarian reserve markers in infertile women with different reserve patterns. STUDY DESIGN:This prospective cross-sectional study included the infertile women attending the Hitit University Hospital. The initial examination included the measurements of waist circumference and hip circumference, body mass index, and waist/hip ratio. A total of 171 women were divided into three groups according to ovarian reserve patterns: (i) adequate ovarian reserve patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Another study proposed that vitamin D receptor polymorphism could play a part in the pathogenesis of PCOS 18 . However, several other studies claim that vitamin D does not have any impact on ovarian reserve markers 19 , 20 . It is therefore still unclear whether low vitamin D levels play a role in the pathogenesis of PCOS, especially in AMH regulation.…”
Section: Introductionmentioning
confidence: 98%
“…Another study proposed that vitamin D receptor polymorphism could play a part in the pathogenesis of PCOS 18 . However, several other studies claim that vitamin D does not have any impact on ovarian reserve markers 19 , 20 . It is therefore still unclear whether low vitamin D levels play a role in the pathogenesis of PCOS, especially in AMH regulation.…”
Section: Introductionmentioning
confidence: 98%
“…The mechanism by which vitamin D may affect AMH and FSH is unclear. Similar to human studies, the findings of experimental studies regarding this association are also inconclusive 66 68 . Vitamin D may influence ovarian steroidogenesis, development of the follicles, and ovarian reserve 7 .…”
Section: Discussionmentioning
confidence: 63%
“…On the contrary, a study showed that there was not a significant correlation between vitamin D/25(OH)D with LH but there was a positive correlation between vitamin D/25(OH)D with FSH in women with adequate ovarium reserve pattern. [40] Other study did not show any correlation between vitamin D/25(OD) and FSH and LH in nonobese, overweight, and obese women. [41] However, other study showed different results that revealed that vitamin D/25(OH)D has an inverse correlation with FSH.…”
Section: Discussionmentioning
confidence: 86%